please help with algebraic manipulation - brain's not working!?

i want to get from (1- v/c)/√(1-v^2/c^2 ) to √((1-v/c)/(1+v/c))

I've tried several times now but i'm not getting anything. A method with all steps shown would be much, much appreciated!!!

Cheers!

?2012-07-29T07:15:08Z

Favorite Answer

The first thing to realize is that 1-v^2/c^2 = (1-v/c)(1+v/c)

The second thing to realize is that (1-v/c) / √(1-v/c) = √(1-v/c).
This is true for any number. 3 / √3 = √3, 4 / √4 = √4, etc.

Keeping these two things in mind, you can solve as has already been shown above:

(1-v/c) / √(1-v^2/c^2)
=
(1-v/c) / √((1-v/c)(1+v/c))
=
(1-v/c) / √(1-v/c) √(1+v/c)
=
√(1-v/c) / √(1+v/c)
=
√((1-v/c) / (1+v/c))

Hope this helps.

Heaven Convergence2012-07-29T12:41:46Z

(1- v/c)/√(1-v^2/c^2 ) = (1-v/c)/√[(1+v/c)(1-v/c)] = √(1-v/c) /√(1+v/c) = √[(1-v/c)/(1+v/c)]